Pengendalian Kualitas Cake dengan Seven Tools di Usaha Ladior, Payakumbuh - Winny Alna Marlina; Habibullah Habibullah; Armijal Armijal (Jurnal Optimalisasi, 2023)
Established in 2002, the Ladior Cake and Cookies MSME operates in the culinary industry, specializing in the production of different kinds of moist cakes and pastries. The company places a strong emphasis on quality control. The company suffered from defective products resulting from quality issues in the production of both wet and dry cakes. Cake flaws include burned cakes, uneven cake sizes, unsightly cakes, easily brittle cakes, and moldy cakes. The purpose of this research is to control cake quality utilizing seven tools. This study is using a quantitative methodology. The research findings indicate that five different types of cake defects were obtained using the check sheet; the highest defects were caused by burnt cake when stratification was applied; the data were obtained using a histogram; the scatter diagram displayed the relationship between the factors causing defects; the Control Chart diagram displayed controlled cake production data; the Pareto diagram identified the defects that required attention, the most critical of which was an empty cake; and the Fish Bone Diagram identified the factors that cause burnt cake defects because the oven needed to be replaced. Factors including Man, Machine, Method, and Material are responsible for the highest number of cake defects out of all product. The Ladior Cake & Cookies owners have to improve maintenance, honing worker professionalism, and stepping up production process oversight to cut down on the amount of faulty goods. Seven tools will be added to the TQM technique by future researchers and used with other MSMEs.